2017
DOI: 10.1007/s12149-017-1224-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone metastatic burden by bone SPECT/CT in metastatic prostate cancer patients: defining threshold value for total bone uptake and assessment in radium-223 treated patients

Abstract: ObjectivesTo establish a new three-dimensional quantitative evaluation method for bone metastasis, we applied bone single photon emission tomography with computed tomography (SPECT/CT). The total bone uptake (TBU), which measures active bone metastatic burden, was calculated as the sum of [mean uptake obtained as standardized uptake value (SUV) above a cut-off level] × (the volume of the lesion) in the trunk using bone SPECT/CT. We studied the threshold value and utility of TBU in prostate cancer patients trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 23 publications
(26 reference statements)
1
40
2
Order By: Relevance
“…SUVs were further higher in our study than those reported by Umeda et al, who found a lower threshold of 7 g/mL of SUV max , above which the tumor burden of metastatic prostate cancer patients was determined [9]. Kuji et al reported a high accuracy of quantitative SPECT/CT for the diagnosis of bone metastases in 170 prostate cancer patients [10].…”
Section: Discussioncontrasting
confidence: 55%
“…SUVs were further higher in our study than those reported by Umeda et al, who found a lower threshold of 7 g/mL of SUV max , above which the tumor burden of metastatic prostate cancer patients was determined [9]. Kuji et al reported a high accuracy of quantitative SPECT/CT for the diagnosis of bone metastases in 170 prostate cancer patients [10].…”
Section: Discussioncontrasting
confidence: 55%
“…Then the average SUVpeak was obtained as the average of the peaks of the regional SUV. 11 When osteosclerotic lesions on bone superscans extended on CT and SUVpeak increased on bone SPECT/CT, the dynamic changes of bone metastases were classified as the new progressive lesions group. When osteosclerotic lesions on bone superscans extended without a SUVpeak increase, or osteosclerotic lesions reduced regardless of SUVpeak changes, the dynamic changes of bone metastases were classified into the only known lesions group.…”
mentioning
confidence: 99%
“…Most single-institution studies (n = 9/25, 36%) originated from the United States; moreover, most of the multi-institutional studies included an American center (n = 6/9, 67%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Five studies originated from Germany [ 23 , 24 , 25 , 26 , 27 ], four from Sweden [ 28 , 29 , 30 , 31 ], and six from Japan [ 32 , 33 , 34 , 35 , 36 , 37 ]. Information about patient number, acquisition technique, type of employed isotope (when applicable) and method of computational analysis were obtainable from all studies.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, a recent work by Umeda et al used quantitative SPECT to establish a SUV threshold, which was used to discriminate metastases from degenerative changes and to compute a “total bone uptake” as a measure of tumor burden [ 37 ]. This value was compared to BSI and resulted slightly more efficient in assessing presence of disease a therapy response.…”
Section: Resultsmentioning
confidence: 99%